REDUCING VENTILATOR-ASSOCIATED PNEUMONIA THROUGH ROTATIONAL VENTILATOR SYSTEM WITHIN LEAN MANAGEMENT FRAMEWORK IN THE ICU OF DR. SOEBANDI HOSPITAL JEMBER - Santika, Suparno Adi; Setijowati, Nanik; Holipah, Holipah (Journal of Community Health and Preventive Medicine, 2025)
Ventilator-associated pneumonia (VAP) is a major nosocomial infection in intensive care units (ICUs). Rotational therapy has been effective in reducing VAP incidence. The high incidence of VAP and the cost of ventilator maintenance indicate the need for a new management strategy. This study aimed to evaluate whether a rotational ventilator system based on lean management principles could reduce VAP incidence. The 5S method (Sort, Set in Order, Shine, Standardize, Sustain) was implemented to facilitate rapid change, while the Plan-Do-Study-Act (PDSA) cycle was used to control process variation and assess effectiveness over a 30-day period. The study involved 259 patients selected through total sampling. Data were analyzed using an independent t-test. Implementation of the revised management flow led to decreased waiting times, reduced non-clinical time wastage, improved patient and family satisfaction, minimized human error, and a 20% reduction in VAP rates within five days. The process was continuously evaluated, refined as needed, and formalized into a standard operating procedure (SOP) and clinical pathway for ICU ventilator management. The rotational ventilator system based on lean management, implemented in the ICU of Dr. Soebandi Hospital Jember, effectively reduced VAP incidence and management costs through the integration of 5S and PDSA methods.